Does situs inversus totalis preclude liver donation in living donor liver transplantation? A series of 3 cases from single institution. (2016) - N., Selvakumar; Goyal, Neerav; Nayeem, Mohammed; Vohra, Sandeep; Gupta, Subash
Highlights: Largest case series with situs inversus totalis. Technique was simple. The critical part of anastomosis was biliary. We have demonstrated all 3 possible biliary anastomosis with technical ease. Outcomes are comparable to the normal right lobes. Abstract: Introduction: Liver transplantation (LT) is the gold standard for decompensated Chronic Liver Disease (CLD) in individuals satisfying the selection criteria. Organ scarcity is the rate limiting step in liver transplantation across the globe. Expanding the donor pool is practiced by transplant surgeons across the globe in view of perennial donor organ scarcity and ever increasing organ demand. Presentation of case: We have presented series of 3 cases of liver transplantation (LT) with modified left lobe (conventional right) graft from a situs inversus donor and implanting it as a conventional right lobe with a modified technique. The grafts had Type 1, Type 2 and Type 3 biliary anatomies. One graft had inferior hepatic veins also. All three patients had uneventful recoveries. The follow up period range is 4 years to 8 months. Discussion: There are multiple case reports in the literature involving situs inversus donors in liver transplantation. Various techniques have also been described. We describe simple and effective technique which has proved successful to our patients. Conclusion: SIT donors can be safely accepted for living donor liver transplantation. It is a technically challenging procedure both for donor liver harvesting and implantation in recipient. This is the first case series of LT using modified left lobe graft (conventional right) from a SIT donor with 2 different techniques. Biliary anastomosis is the tricky part of the operation.